The Reciprocal Strategy to Improve Students’ Reading Comprehension - Inya, Leni Tamo; Suhartatik, Suhartatik (UIBU, 2023)
The challenge of literacy often serves as a significant barrier for students in accessing knowledge and realizing their full potential. This research stems from a deep concern regarding the low reading comprehension of students at SMP Negeri 3 Lamboya, West Sumba, NTT. The study aims to enhance students’ reading comprehension by using Reciprocal strategy. It is not merely a set of techniques, but an empowering, dialogue-based approach that trains students to assume active roles as critical thinkers and inquirers, focusing on four pillars: Summarizing, Questioning, Clarifying, and Predicting. This study involves 30 students across two cycles, focusing on gradual training and the intentional transfer of discussion leadership from the teacher to the students.The findings reveal a significant and palpable improvement, evident both quantitatively (increased test scores from pre-cycle to Cycle I and Cycle II) and qualitatively (increased student enthusiasm in discussions, greater confidence in asking questions, and the ability to self-monitor comprehension difficulties). The strategy has proven to be effective not only in boosting reading comprehension but also in fostering self-confidence and collaborative skills among the students.